Integration of Ushul al-Fiqh in the Indonesian Legal System: A Study on the Role of the Indonesian Republic Supreme Court - Arip Purkon (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article examines the integration of u??l al-fiqh principles in the Indonesian legal system through the role of the Indonesian Republic Supreme Court as the highest judicial institution. The study focuses on how the Supreme Court adopts and applies the concepts of maq??id al-shar??ah, ma?la?ah, qiy?s, and isti?s?n in judicial reasoning and the development of jurisprudence. This research employs a normative legal research method using conceptual and case approaches. Data were collected through library research, including the study of u??l al-fiqh literature, statutory regulations, and an analysis of selected Supreme Court decisions concerning Islamic family law and Islamic economic law. The findings demonstrate that the Supreme Court does not merely apply positive law textually but also employs the principles of u??l al-fiqh as a basis for legal reasoning to achieve substantive justice and public welfare. This integration is evident in cases involving interfaith inheritance, marriage annulment, and Islamic economic disputes. Although challenges remain, including legal pluralism, the predominance of positivistic legal approaches, and the limited methodological understanding of some judicial officers, the integration of u??l al-fiqh holds significant potential to strengthen the harmonization of Islamic law and the national legal system. This study concludes that the Supreme Court has played a pivotal role in developing jurisprudence that is adaptive, inclusive, and oriented toward the objectives of Islamic law within the framework of Indonesia's constitutional state.